2003
DOI: 10.1136/ip.9.2.138
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of hip protector use by frail older women living in their own homes

Abstract: Objectives:To investigate the efficacy and effectiveness of hip protectors in frail community living older women.Design:Randomised controlled trial.Setting:Aged care health services in New South Wales, Australia.Patients:600 women 74 years of age or more (mean age 83 years), who had two or more falls or one fall requiring hospital admission in the previous year, and who lived in their own homes.Intervention:Use of hip protectors.Main outcome measures:Adherence with use of hip protectors, falls, incidence of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
2
14

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 11 publications
1
47
2
14
Order By: Relevance
“…Making definitive comparisons between studies is difficult, as compliance has been measured in many different ways [24]. However, seven randomised controlled studies provided the rate of wearing hip protectors at the time of fall (24-74%) [11][12][13][14][16][17][18]. The level of compliance achieved in this study was superior to previous studies, particularly in terms of the percentage of falls protected with hip protectors (85.3%, Table 5).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Making definitive comparisons between studies is difficult, as compliance has been measured in many different ways [24]. However, seven randomised controlled studies provided the rate of wearing hip protectors at the time of fall (24-74%) [11][12][13][14][16][17][18]. The level of compliance achieved in this study was superior to previous studies, particularly in terms of the percentage of falls protected with hip protectors (85.3%, Table 5).…”
Section: Discussioncontrasting
confidence: 51%
“…To date, at least 15 randomised controlled trials (RCTs) examining the effect of external hip protectors on incidence of hip fractures have been published. Hip protectors led to a significant reduction in the incidence of hip fractures in five studies [8][9][10][11][12] while results were borderline significant in two studies [13,14] and no significant reduction in hip fracture incidence was seen in eight studies [15][16][17][18][19][20][21][22]. These discrepancies among RCTs might be attributable to differences in the methods of randomisation, biomechanical properties of the actual hip protectors used and compliance rates for use of hip protectors.…”
mentioning
confidence: 84%
“…Finally, we have used this approach to highlight the effectiveness of hip protectors in decreasing the risk of hip fractures in a vulnerable, often ignored population with a significant burden of disease. Process of exclusion of studies from the systematic review [26][27][28][29][30][31][32][33][34][35][36]. Table 1 Assessment of the methodologic features of included studies The unit of randomization was not clearly described in the primary publication.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were all measured by the recall of the participant if he or she was living in the community or from records in the hospital ward for the time that the participant had spent in hospital. These methods have been successfully used by the investigators in other studies [22,23].…”
Section: Discussionmentioning
confidence: 96%
“…There have been three randomised trials reporting the effectiveness of hip protectors [22,28,29] for this group, and the pooled result of these studies showed no effect in reducing hip fractures [7]. The main reason for lack of effect suggested by these studies was that incomplete adherence meant that overall effectiveness could not be established.…”
Section: Discussionmentioning
confidence: 99%